1996
DOI: 10.1097/00006534-199610000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Analysis of Breast and Periprosthetic Capsular Tissue from Patients with Saline or Silicone Gel Breast Implants

Abstract: The ubiquitousness of silicon is well known. Recent work has demonstrated measurable baseline levels of silicon in nonaugmented cadavers, subsequent to numerous reports of significant elevations of such levels within patients with silicone breast implants and even more reports alleging a causal relation between silicone gel prostheses and connective-tissue diseases. Despite the lack of scientifically substantiated data that such a relation exists, the calamitous silicone breast implant controversy has ensued. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 8 publications
0
17
0
2
Order By: Relevance
“…In this study, no correlation was found between the amount of silicon measured in the capsular tissue surrounding the implant and the length of implantation time, as determined by linear regression (r 2 ϭ 0.02) and Pearson correlation test (r ϭ 0.22). Several studies have shown an increase in the concentration of silicon in tissue with increasing implantation time (27,28). This is supported by estimates of the mean-life time of a breast implant, about 10 to 12 years (5,6).…”
Section: Quantitation Of Pdmsmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, no correlation was found between the amount of silicon measured in the capsular tissue surrounding the implant and the length of implantation time, as determined by linear regression (r 2 ϭ 0.02) and Pearson correlation test (r ϭ 0.22). Several studies have shown an increase in the concentration of silicon in tissue with increasing implantation time (27,28). This is supported by estimates of the mean-life time of a breast implant, about 10 to 12 years (5,6).…”
Section: Quantitation Of Pdmsmentioning
confidence: 77%
“…Measurements performed on different portions of the same capsule varied by as much as a factor of two (see Table 1). Atomic absorption studies have also shown high levels of silicon in capsular tissue (26)(27)(28); however, the identity of the compound containing the silicon could not be confirmed because of the inability of the technique to determine chemical structure. The lowest concentration of silicon calculated was 0.05%.…”
Section: Quantitation Of Pdmsmentioning
confidence: 99%
“…35 That document addresses in detail the differences in silicon concentrations observed in tissues surrounding saline and silicone gel-filled implants from different manufacturers and the clinical implications of this work. Here, we discuss the analytical issues involved in the development and evaluation of the method for silicon analysis in tissue and compare tissue silicon concentrations with histologic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Las roturas protésicas extracapsulares tienen un alto potencial de migración o captación linfática de la silicona pudiendo producirse granulomas en el área tóraco-mamaria y/o adenopatías axiliares siliconomatosas. Schnur et al(1996) (9), encuentran que los niveles de silicona en el tejido capsular periprotésico son significativamente elevados en las pacientes portadoras de implantes mamarios rellenos de silicona aunque las prótesis se encuentren indemnes; si existe una rotura intracapsular los niveles de silicona están elevados también en el tejido mamario. Holmich y colaboradores (2001) (10), hallan que inicialmente 3 de cada 4 rupturas (75%) son intracapsulares y 1 de cada 4 (25%) son extracapsulares.…”
Section: Discussionunclassified
“…Estos dos últimos hechos, tamaño y dinámica, producen un aumento en la fatiga del material con un mayor desgaste de la superficie de la prótesis (fricción dinámica) y liberación de partículas de silicona desde la superficie de la misma. Quienes han recambiado prótesis mamarias seguramente habrán observado, ocasionalmente, en algunas partes de la cubierta un mayor desgaste de la superficie de la misma con desaparición parcial de la texturixación, lo que es un indicador de microliberación de partículas de silicona (9). El rozamiento y la basculación de la prótesis producidos por el movimiento muscular (repetición y carga) pueden, además de suavizar la texturización y modificar el posicionamiento (giros en el eje vertical y horizontal de la prótesis), inducir un encapsulamiento más rígido, pliegues en la próte-sis, seroma tardío, rotura protésica y adenitis siliconomatosa.…”
Section: Discussionunclassified